2020
DOI: 10.1063/1.5131501
|View full text |Cite
|
Sign up to set email alerts
|

Observation of quincunx-shaped and dipole-like flatband states in photonic rhombic lattices without band-touching

Abstract: We demonstrate experimentally the existence of compact localized states (CLSs) in a quasi-one-dimensional photonic rhombic lattice in presence of two distinct refractive-index gradients (i.e., a driven lattice ribbon) acting as external direct current (dc) electric fields. Such a lattice is composed of an array of periodically arranged evanescently coupled waveguides, which hosts a perfect flatband that touches both remaining dispersive bands when it is not driven. The external driving is realized by modulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…where [81] lattices with different boundary terminations, (C-E) Kagome lattices with different boundary terminations [86], (F) a superhoneycomb lattice [85], and (G) a "driven" rhombic lattice with an index gradient [84].…”
Section: Numerical Methods and Flat-band Classificationmentioning
confidence: 99%
See 4 more Smart Citations
“…where [81] lattices with different boundary terminations, (C-E) Kagome lattices with different boundary terminations [86], (F) a superhoneycomb lattice [85], and (G) a "driven" rhombic lattice with an index gradient [84].…”
Section: Numerical Methods and Flat-band Classificationmentioning
confidence: 99%
“…Flat-band states have also been demonstrated in a rhombic lattice that is robust in the presence of an external driving field (index gradient) along the lattice axis by Mukherjee and Thomson [38]. Recently, Xia et al [84] demonstrated the existence of CLSs in a driven rhombic lattice ribbon with two distinct refractive index gradients acting as external dc fields. Such CLSs span over two unit cells with a quincunx shape under the action of a driving force.…”
Section: A B Cmentioning
confidence: 98%
See 3 more Smart Citations